Hantavirus infections in Italy: not reported doesn’t mean inexistent. - Riccò, Matteo; Peruzzi, Simona; Ranzieri, Silvia; Balzarini, Federica; Valente, Marina; Marchesi, Federico; Bragazzi, Nicola Luigi (Acta Biomedica Atenei Parmensis, 2021)
Background. Hantaviruses can cause serious human diseases including hemorrhagic fever with renal syndrome (HFRS) and Hantavirus Cardiopulmonary Syndrome (HCPS). European Hantavirus are usually associated with HFRS, and their geographical distribution mirrors the ecology of reservoir host species. Epidemiology of HFRS is well-studied in Western Europe, but data from Italy are fragmentary.Methods: We searched into two different databases (PubMed and EMBASE), focusing on studies reporting the prevalence of Hantaviruses in Italy. Data were extracted using a standardized assessment form, and results of the analyses were systematically reported, summarized and compared.Results. We identified a total of 18 articles, including 12 reports (total population: 5,336 subjects, 1981-2019) and 6 case reports (1984-2019). In total, 200 subjects exhibited some degree of seropositivity, with a pooled seroprevalence of 1.7% (95% confidence interval 0.7%-4.0%) in the general population. Higher occurrence was reported in selected subgroups, i.e. acute (28.7%, 95%CI 22.1-36.2) and chronic (6.6%, 95%CI 4.7-9.1) renal failure, forestry workers (3.0%, 95%CI 1.4-6.5, actual range 0.0 to 10.8%).Conclusions. In the last decade, no human cases of hantavirus infection have been officially reported in Italy. However, our analysis stresses the actual occurrence of Hantavirus among general population and in selected population groups. Further studies on hantavirus infection rates in reservoir host species (rodents, shrews, and bats) and virus transmission to humans are needed to prevent outbreaks in the future.